Stabbed in the baklava - Kashian, Tina (Kashian, Tina. Kebab Kitchen mystery., 2018)
Catering a high-society wedding should bring in some big income for Kebab Kitchen<U+2014>and raise its profile too. But it<U+2019>s not exactly good publicity when the best man winds up skewered like a shish kebab. Worse yet, Lucy<U+2019>s ex, Azad<U+2014>who<U+2019>s the restaurant<U+2019>s new head chef<U+2014>is the prime suspect. But she doesn<U+2019>t give a fig what the cops think. He may have killer looks, but he<U+2019>s no murderer. She just needs to prove his innocence, before he has to go on the lamb . . .